The increasing incidence and mortality of bacteremia in Denmark from 2010 to 2022: a population-based nationwide cohort study - Dessau, Ram B.; Andersen, Christian Østergaard; Coia, John; Ellermann-Eriksen, Svend; Gubbels, Sophie; Jensen, Thøger Gorm; Knudsen, Jenny Dahl; Kähler, Jonas; Lomborg, Steen; Lützen, Lisbeth; Nielsen, Marc Trunjer Kusk; Olesen, Bente Scharvik; et al. (Frontiers in Public Health, 2024)
ObjectivesAn increasing incidence of positive blood cultures has been reported in several countries. This represents an important challenge for public health due to the large number of hospital admissions with high mortality among these patients. This study aims to characterize the epidemiology and mortality associated with positive blood cultures.Study design and methodsWe performed a nationwide cohort study, identifying all individuals with a blood culture drawn in Denmark from 2010 to 2022. We estimated the incidence of positive blood cultures and 30-day mortality per 100,000 individuals and modeled the case fatality rate (CFR) and population incidences with regression techniques.ResultsWe identified almost 4 million blood cultures drawn during the study period, increasing 64% from 220,757 in 2010 to 362,239 in 2022. During this period, the underlying population increased only 10%, whereas the population of older adults above 85 years increased 3.3 times. The positivity rate was 9.8%, and the most common pathogens were Escherichia coli (29%) and other pathogens associated with urinary tract infection, whereas Staphylococcus aureus accounted for 12%, and Enterococcus faecium for 4.1%. The 30-day CFR was 17% with a small reduction during the study period, with notable differences according to species.ConclusionWe found a substantial rise in blood culture activity and the incidence of positive cultures. This rise is driven by an increasing number of older citizens, which is expected to increase further in the coming years. Considering the high risk of mortality and increasing incidence, a national surveillance of bacteremia is warranted.